Communication and humanization of care: Effects over burnout on nurses - Molero Jurado, María del Mar; Herrera Peco, Ivan; Pérez Fuentes, María del Carmen; Oropesa Ruiz, Nieves Fátima; Martos Martínez, África; Ayuso Murillo, Diego; Gázquez Linares, José Jesús (My University, 2021)
Background Healthcare professionals may have certain psychological characteristics which contribute to increasing the quality of their professional performance. Objective Study the effect that humanization of care and communication have on the burnout syndrome in nursing personal. Methods The sample included a total of 330 Spanish nurses. Analytical instruments used were the Health Professional¿s Humanization Scale (HUMAS), Communication Styles Inventory Revised (CSI-R) and Brief Burnout Questionnaire Revised (CBB-R). Results Two broad nursing profiles could be differentiated by their level of humanization (those with scores over the mean and those with scores below it in optimistic disposition, openness to sociability, emotional understanding, self-efficacy, and affection), where the largest group had the high scores. A communication repertoire based on verbal aggressiveness impacted indirectly on the effect of humanization on burnout, mainly in the personal impact component. We observed the relation of humanization profiles in nursing staff with the job dissatisfaction and burnout components. Besides that, some communication styles, verbal aggressiveness and questioningness, have an indirect effect on the relationship between humanization profiles and job dissatisfaction. Conclusions The results on the relationship between communication styles and burnout, and the mediator effect of communication styles on the relationship between humanization of care and burnout in nursing personnel are discussed.